Α1‐Blocker inhibits non‐voiding contractions and decreases the level of intravesical prostaglandin E2 in rats with partial bladder outlet obstruction. (17th July 2019) - Akino, Hironobu; Ito, Hideaki; Nagase, Keiko; Matsuta, Yosuke; Aoki, Yoshitaka; Hattori, Tsuyoshi; Yokoyama, Osamu
Abstract : Objectives: To elucidate the mechanism of action of the α1 ‐blocker, naftopidil, in partial bladder outlet obstruction animals, by studying non‐voiding contractions, and the levels of mediators were measured with resiniferatoxin treatment. Methods: A total of 35 female Wistar rats were randomly divided into a sham or bladder outlet obstruction group, and rats in each group were given vehicle or resiniferatoxin. Incomplete urethral ligation was applied to the bladder outlet obstruction group. After cystometry, the intravesical level of prostaglandin E2 and adenosine 5′‐triphosphate was measured in the instilled perfusate collected. Naftopidil was given at the time of cystometry. Results: In bladder outlet obstruction rats, non‐voiding contractions, bladder capacity, and the intravesical levels of prostaglandin E2 and adenosine 5′‐triphosphate were markedly increased compared with sham rats. Naftopidil decreased non‐voiding contractions, enlarged the bladder capacity, and decreased the intravesical levels of prostaglandin E2 and adenosine 5′‐triphosphate. Resiniferatoxin enhanced non‐voiding contractions. The effects of naftopidil on non‐voiding contractions and the intravesical level of prostaglandin E2, but not adenosine 5′‐triphosphate, were tolerant to resiniferatoxin. Conclusions: In bladder outlet obstruction rats, one cause of generation of non‐voiding contractions might be bladder wall distension, but not transient receptor potential cation channel V1. The increase in intravesical prostaglandin E2 might also be associated with the generation of non‐voiding contractions. Naftopidil inhibits the increase in non‐voiding contractions and decreases the intravesical level of prostaglandin E2, which are independent of transient receptor potential cation channel V1.